2015
DOI: 10.1016/j.tate.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Teacher interpersonal behaviour and student motivation in competence-based vocational education: Evidence from Indonesia

Abstract: h i g h l i g h t sPerceived teacher interpersonal behaviour (TIB) predicts student motivation. TIB connects competence-based education (CBE) and student motivation. Impact of TIB on student motivation is greater in less-CBE than in CBE context. a b s t r a c tCompetence-based education requires changing teacher roles probably affecting teacherestudent interactions and student motivation. This study examines how students (N ¼ 1469) from competencebased and less-competence-based vocational schools perceive thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 34 publications
3
43
0
2
Order By: Relevance
“…Indonesian vocational schools have gained much popularity and supports from several social factors. However, the most important support is from parents (Misbah, Gulikers, Maulana, & Mulder, 2015;Newhouse & Suryadarma, 2011). Most parents believe that if their children are enrolled in vocational schools, they will gain more advanced skills and thus have an advantage over those who enroll in general high schools (Misbah et al, 2015).…”
Section: Korean Socio-cultural Background Related To Stem Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Indonesian vocational schools have gained much popularity and supports from several social factors. However, the most important support is from parents (Misbah, Gulikers, Maulana, & Mulder, 2015;Newhouse & Suryadarma, 2011). Most parents believe that if their children are enrolled in vocational schools, they will gain more advanced skills and thus have an advantage over those who enroll in general high schools (Misbah et al, 2015).…”
Section: Korean Socio-cultural Background Related To Stem Educationmentioning
confidence: 99%
“…However, the most important support is from parents (Misbah, Gulikers, Maulana, & Mulder, 2015;Newhouse & Suryadarma, 2011). Most parents believe that if their children are enrolled in vocational schools, they will gain more advanced skills and thus have an advantage over those who enroll in general high schools (Misbah et al, 2015). Perhaps because of this, the number of vocational school students in Indonesia exceeded the number of general high-school students in 2015 (JPPN, 2015).…”
Section: Korean Socio-cultural Background Related To Stem Educationmentioning
confidence: 99%
“…Despite a growing number of studies on the effectiveness of teaching and quality within the vocational education context (e.g. Misbah et al, 2015;Placklé et al, 2014), the higher vocational education context is under-represented. Therefore, the research reported here aims to respond to this gap in the literature by contributing to the practical knowledge of quality teaching within a Maltese higher vocational education institution.…”
Section: Introductionmentioning
confidence: 99%
“…In competence-based education, students should be challenged more to perform complex, vocational problems and guide their own learning process without being this dependent on their teachers (Sturing et al 2011). Thus, the way students and teachers interact in their regular educational practice needs to be addressed for a proper implementation of these assessments as an integral part of the curriculum (Misbah et al 2015) as well as for preparing students for independent performance of occupational tasks expected in VET (EQF level 4; see described in the 'research context').…”
Section: Conclusion and Discussionmentioning
confidence: 99%